PENGEMBANGAN MEDIA INTERAKTIF ARTICULATE PADA MATA PELAJARAN INFORMATIKA MODEL 4 D - Wuliadi; Rufi’i; Reza Rachmadtullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop Articulate Interactive Media for Informatics at SMPN 3 Ngoro Satu Atap using the 4D development model (Define, Design, Develop, Disseminate). The Define stage identifies student needs, objectives, and characteristics. The Design stage includes designing the flow, appearance, and content of the media. The Develop stage includes media creation, validation by material and design experts, and revisions. The Disseminate stage involves limited trials and usability evaluations. Data were collected through validation sheets, documentation, and observations, then analyzed descriptively and quantitatively to assess the feasibility of the material, design, technical aspects, and learning benefits. The results indicate that the developed interactive media is highly feasible for use. Experts gave high scores for material suitability, content accuracy, appearance, interactivity, and ease of use. This media increases student motivation, engagement, and understanding, and has the potential to become an innovative model in the development of 21st-century interactive learning media.